1987
DOI: 10.1037/0022-3514.53.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Social or evolutionary theories? Some observations on preferences in human mate selection.

Abstract: In this article, we extend the research by Buss and Barnes (1986) on preferences in human mate selection. Buss and Barnes explored human mate preferences by identifying major dimensions of preferences, sex differences in selection preferences, and the relations between mate preferences and characteristics of obtained partners. To examine these questions, Buss and Barnes studied two heterosexual samples. In discussing their findings, they specified two general theoretical orientations to understanding human mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 10 publications
3
79
0
Order By: Relevance
“…This fact corresponds with the theory saying that men offer social status and women physical beauty (e.g. Berry & Miller, 2001;Buss, 1989;Howard et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact corresponds with the theory saying that men offer social status and women physical beauty (e.g. Berry & Miller, 2001;Buss, 1989;Howard et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Berry & Miller, 2001;Buss, 1989;Howard, Blumstein & Schwartz, 1987) and that, in opposite, women would prefer men who had an attractive socio-economic status (Berscheid & Walster, 1974;Klein, 1991;Townsend & Wasserman, 1997). These differences in partner preferences had been explained in terms of social role theory (e.g.…”
mentioning
confidence: 99%
“…It has been reported that homosexual men show male-typical mating psychology, including interest in casual sex and visual sexually explicit material (Bailey, Gaulin, Agyei, Gladue 1994); they also report male-typical mate retention behavior (Vanderlaan, Vasey 2008), prefer potential partners who are younger than themselves (Hayes 2001, Silverthorne, Quinsey 2000 and, again similarly to heterosexual men, value physical attractiveness in their potential partners more than heterosexual women (Howard, Blumstein, Schwartz 1987). On the other hand, homosexual men prefer as partners men who describe themselves as rather masculine, and this is dependent on their own level of masculinity (Bailey, Kim, Hills, Linsenmeier 1997, Muscarella 2002.…”
Section: Effect Of Male Masculinity-femininity In Same-sex Preferencesmentioning
confidence: 99%
“…For instance, studies have examined preferences for traits like ''ambitiousness'' (Howard, Blumstein, & Schwartz, 1987;Hoyt & Hudson, 1981;Hudson & Henze, 1969;McGinnis, 1958), ''good earning capacity'' (Buss, 1989;Stewart, Stinnett, & Rosenfeld, 2000), ''good financial prospects'' (Buss, 1989), ''educated'' (Greitmeyer, 2005;Kenrick, Sadalla, Groth, & Trost, 1990;Lance, 1998), having high ''social status,'' ''social level, '' or ''prestige'' (Feingold, 1992;Townsend & Levy, 1990;Townsend & Wasserman, 1998) -traits thought to be related to one's ability to generate income. Consistently, women value mates with these traits more than men do (Townsend, 1993;Townsend & Roberts, 1993).…”
Section: Preferences For Resourcesmentioning
confidence: 99%